Factors related to negative feelings experienced by emergency department patients and accompanying persons: an Israeli study - Simha F. Landau; Judy Bendalak; Gila Amitay; Ohad Marcus (BMC, 2018)
Abstract Background Studies on hospital violence have emphasized the importance of staff- service recipient interaction in leading to violent incidents. These incidents are the extreme result of service recipients' frustration and anger in their interaction with staff. The aim of this study was to analyze factors related to negative experiences of emergency department (ED) patients and accompanying persons in Israeli hospitals. Methods Structured interviews with 692 participants in seven major general Israeli hospitals: 322 patients and 370 accompanying persons. Results Negative feelings while in the ED were reported by 23.6% of patients and 20.5% of accompanying persons. Eight aggregate variables relating to staff-patients/accompanying persons interaction were identified: 1. General attitudes of staff and quality of ED experience; 2. Staff attitudes towards patients; 3. Staff attitudes towards accompanying persons; 4. Waiting; 5. Quality of perceived medical care; 6. Information provided to patients and accompanying persons; 7. Information provided to patients, as reported by accompanying persons; and 8. Severity of medical problem. Among patients, the only significant aggregate variable related to anger and frustration was perceived quality of care. Among accompanying persons, the three significant contributors to negative feelings were: 1. Staff's general attitudes; 2. Attitudes towards patients; and 3. Severity of patients' medical problem. Analysis of specific items within the variables revealed that, whereas patients' negative feelings were related to nurses' perceived negative attitudes those of accompanying persons were related to the doctors' perceived negative attitudes. In addition, patients' negative feelings were related to low severity of medical problem, whereas accompanying persons' negative feelings were related to patients' low severity of pain. Conclusions The study reveals the importance of including both patients and accompanying persons in the analysis of staff-service recipient interactions in EDs. The results are discussed in terms of patients' and accompanying persons' different perspectives. Three practical implications of the results are put forward, aiming at reducing patients/accompanying persons-staff frictions in the EDs, thus decreasing the potential of violent outbursts against ED staff: (1) implementing a framework based on "patient-centeredness" for the restoration of patient's sense of agency and empowerment; (2) broadening the scope of laws concerning patient's rights to include their families and other accompanying persons; and (3) implementing courses on interpersonal and human service skills, as well as teaching skills of handling emotional stressors experienced by both the staff and service recipients.